Kajian Penerapan Produksi Bersih di Stasiun Gilingan pada Proses Produksi Gula - Puspita Yuliandari; Anas M. Fauzi; Suprihatin Suprihatin; Ono Suparno (Universitas Bunda Mulia, 2017)
The development of sugar industries in Indonesia is influenced by the capability of increasing sugar productivity every year. This increasing is important to handle problem that happened. One of the solutions of the problem, such as sugar loss and inefficiency energy was application of the cleaner production. PG. Tersana Baru have been doing efforts to minimize fuel consumption in milling station. This research objective were to design a processing improvement in milling station through cleaner production approach strategy in reducing sugar loss and increasing energy (steam and fuel) uses efficiency and to build a dynamic model on the influence of imbibitions water to water content of bagasse and sucrose content in milling station at PT. PG. Rajawali II Unit PG. Tersana Baru, West Java. The results of this research indicated a potency for application of a cleaner production approach in PG. Tersana Baru based data collected during 2007 milling season, of which the optimum of imbibitions water was 22.64 %. That condition was achieved in the 8th period of production with fuel energy consumption of 298,466 kcals/ton sugar cane. At this condition, there was possibility for annual energy consumption to be reached by 227,418 kcal/ton sugar cane or equivalent to Rp 764,184,666,153.00. The addition of water imbibitions at the milling process in the dynamic system simulation model was carried out at the interval of 21.20 – 35%. The results in water contents of bagasse of 49.21 – 62.74% and its sucrose contents of 0 – 5.18%.Keywords: Cleaner Production Approach, Imbibitions Water, Efficiency Energy Consumption, Dynamic System Simulation Model